A new concept regarding the cause of ionosphere semiannual and annual anomalies - Azpilicueta, Francisco Javier (2011)
Since the beginning of the pioneering scientific work on the ionosphere, unusual responses have been reported and have been named semiannual and annual anomalies owing to their unexplained and periodic nature. Despite more than 60 years of scientific and technological achievements, a definitive explanation for these intriguing phenomena has not been found, and, on the contrary, similar anomalies have been found in other geophysical phenomena. The best candidate for the driving force behind the anomalies is the solar wind, but contemporary theories of the behavior of Earth's magnetosphere preclude the description of a causal mechanism. Here we present a mechanism of energy transfer from the magnetosphere to the ionosphere that can explain both anomalies. The importance of this theory is that it makes available a secondary source of energy to Earth's upper atmosphere and ionosphere; that energy could constitute as much as 40% of the energy budget in the ultraviolet and extreme ultraviolet regions of the solar electromagnetic spectrum. This will be of importance to thermospheric, ionospheric, magnetospheric, and space physics research.